INVESTASI PERKEBUNAN KARET DAN KESEJAHTERAAN KARET DI KALIMANTAN BARAT - B61111011, MARISA MEIRATANIA (Jurnal Ekonomi Daerah (JEDA), 2017)
This study has the following objectives : 1) To test and analyze the feasibility of investment in rubber plantations in West Kalimantan, 2) To analyze the impact of investments on the level of welfare rubber rubber farmers in West Kalimantan. This research uses descriptive quantitative approach with survey method.Â  The data used are primary data with 60 respondents of Kubu Raya, Sintang and Ketapang. The results of the research, it turns out investments rubber plantations in West Kalimantan viable because based on the criteria Net Present Value (NPV) showed positive figures, and based on the criteria of Net Benefit Cost Ratio (Net B / C) indicates the number of 3.22, then the criteria Internal Rate of Return (IRR) showed a greater rate of return than the interest rate applicable. Welfare rubber farmers in West Kalimantan included in being seen from the level of consumption of rubber farmers, showed that the level of welfare of rubber farmers included in the group of moderate prosperity level (Criterion Gilarso) as of 60 respondents 75% indicated their food expenditure in between 40% -75% and 25% of respondents have food expenditure greater than 75% are included in the category of welfare levels are low. Keywords : Investment feasibility and welfare Farmer